STUDENTS’ COMPREHENSION IN ENGLISH MEDICAL TERMINOLOGY AT KHAIRUN UNIVERSITY - Mutia Harun; Taib Latif; Roswita M. Aboe; Fitria Wulan Sari (FKIP Universitas Khairun, 2023)
This study aims to determine the understanding of medical students about English medical terminology. This study used descriptive quanitative method. There were 21 medical students at Khairun Ternate University who were involved in this research. By using purposive sampling technique. . Data was collected by using a test and questioner via google form. Of the 21 students, only 4 students got good grades, the other 17 were very low. The results of this study indicate the average value of students is 49.7 in the poor category.